DESAIN BATIK AKSARA JAWA PADA PENGRAJIN BATIK BERKAH LESTARI GIRILOYO, WUKIRSARI, BANTUL - Zulfi Hendri, Hesti Mulyani, Venny Indria Ekowati (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
The aim of providing training to be able to implement Javanese script asbatik motif on mori material that can be read and written in the right way. Inaddition, to provide training to be able to use Javanese script as the batik motifon mori material in better designs to attract buyers.This activity was applied in the form of training and mentoring. The firstmaterial given in the training is the introduction of batik. The second material isaround the Javanese script and grammar. Mentoring was performed to determinethe success level of the training of Javanese script writing, designing, andcoloring. Mentoring activities is important and needs to be done to anticipatewriting errors and colouring mismatches.This resulted four different forms of written batik. Those areas follow:(1) hem pattern materials, Javanese script writing, is legible and was writtencorrectly according to the rules of Javanese script writing; (2) extended was writtencorrectly according to the rules of Javanese script writing; (3) extended tablecloths,the words on it was written correctly according to the rules of Javanesescript writing; and (4) extended scarf with Javanese script. In terms of coloring,it was already good, meaning that the results of the four pieces of batik arewell-done.